Translating research into policy: the case of orphans and vulnerable children in South Africa - Olive Shisana; Julia Louw (Taylor & Francis Group, 2006)
Policies are often developed without taking into account social science research findings and recommendations, despite the plethora of such research studies. This is largely because researchers and policy makers often work in isolation, yet if they worked synergistically they could have a significant impact on implementing interventions known to work to improve the lives of populations. Several approaches have been advanced to encourage policy makers to take heed of scientific findings and to urge scientists to take into account the needs of policy makers in designing their research agenda. This paper aims to illustrate how policy has been informed using the case study of the Orphans and Vulnerable Children project in South Africa. It further highlights the successes and challenges encountered thus far with this project. In some countries, particularly those of the north, there has been major progress in bridging this gap between research and policy; however, in developing countries much remains to be done.